The Impact of Implementing the Lexical Approach on EFL Students’ Writing Skills at Salahaddin University-Erbil - Rebin Abdulqader Azeez; Qismat Muhammed Hussin (Zanco Journal of Human Sciences, 2026)
The effectiveness of the Lexical Approach in improving the writing skills of Kurdish EFL students at Salahaddin University in Erbil is examined in this study. Based on Lewis's (1993) theory that views language as "grammaticalised lexis," the study investigates whether teaching lexical chunks, collocations, and prefabricated expressions can improve general writing proficiency as well as the fundamental skills of complexity, accuracy, and fluency. With 100 second-year university students, a quasi-experimental design was adopted. The experimental group received lexical exercises aimed at improving CAF by extensive exposure to the Lexical Approach, whereas the control group received instruction using a conventional, non-lexical method. Although both groups improved their writing abilities, the experimental group performed noticeably better than the control group on tests of complexity, syntactic diversity, and the proper use of target lexical pieces in a variety of sentence constructions. Both alternative hypotheses were confirmed and relate to previous studies in similar EFL settings overseas, highlighting the didactic importance of teaching lexical phrases. However, statistical analysis using SPSS clearly showed significant improvements for the experimental group across all aspects of writing and facets of complexity, accuracy, and fluency, with a remarkably higher post-test average variation of 24.32 points between the two clusters (p < 0.001). According to the findings, the Lexical Approach is a successful and regionally appropriate method for advancing EFL writing proficiency in Kurdish colleges. Implications include improved student writing, better language learning results, and the possibility of raising the standard of English instruction in Kurdistan. Future research that replicates this work, however, would contribute to further confirming the effectiveness of this strategy in various educational settings.